2008
DOI: 10.2136/sssaj2007.0201
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Organic Carbon in Sediment Transport by Interrill and Rill Erosion Processes

Abstract: Erosion and loss of organic carbon (OC) result in degradation of the soil surface. Rill and interrill erosion processes on a silt loam soil were examined in laboratory rainfall and flume experiments. These experiments showed that rill and interrill erosion processes have contrasting impacts on enrichment of OC in transported sediment. Rill erosion was found to be nonselective, while for interrill erosion the enrichment ratio of OC, EROC, varied between 0.9 and 2.6 and was inversely related to the unit sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 40 publications
(35 reference statements)
11
99
2
1
Order By: Relevance
“…(7) is used to estimate the transport for sediment delivered to the rill network (or that leaves a grid cell when there is no incised rill). This approach is consistent with empirical observations showing that the enrichment of finer sediment particles and SOC in suspended sediment is mainly controlled by the transport capacity of the flow (Schiettecatte et al, 2008a). To represent the amount of primary particles vs. soil aggregates of suspended sediments, the model interpolates the settling velocity for each particle class and grid cell according to the proportion of particles detached by interrill or rill erosion.…”
Section: Modelling Erosion and Depositionsupporting
confidence: 78%
See 1 more Smart Citation
“…(7) is used to estimate the transport for sediment delivered to the rill network (or that leaves a grid cell when there is no incised rill). This approach is consistent with empirical observations showing that the enrichment of finer sediment particles and SOC in suspended sediment is mainly controlled by the transport capacity of the flow (Schiettecatte et al, 2008a). To represent the amount of primary particles vs. soil aggregates of suspended sediments, the model interpolates the settling velocity for each particle class and grid cell according to the proportion of particles detached by interrill or rill erosion.…”
Section: Modelling Erosion and Depositionsupporting
confidence: 78%
“…interrill erosion detaches and transports primary particles, whereas rill erosion is unselective and detaches and transports soil aggregates. The concept of particle size-selective interrill and nonselective rill erosion which detaches and entrains the entire soil matrix has been documented in numerous studies (Kuhn et al, 2010;Polyakov and Lal, 2004;Quinton et al, 2001;Schiettecatte et al, 2008a). Following non-selective splash erosion (Poesen and Savat, 1980;Poesen, 1985;Parsons et al, 1991), selectivity is caused by particle size specific deposition differences, where coarser and heavier particles settle out earlier than finer and lighter particles (Schiettecatte et al, 2008b).…”
Section: Sediment and Carbon Mobilization And Export Under Different mentioning
confidence: 99%
“…While catchment C1 follows the expected behaviour, i.e. decreasing SOC enrichment with increasing event size (Auerswald and Weigand, 1999;Menzel, 1980;Polyakov and Lal, 2004b;Sharpley, 1985), and is in good agreement with the results of Wang et al (2010) for similar soils in the Belgian loam belt, event size had hardly any effect on the SOC enrichment in catchment C2, where any larger particles, including aggregates, are deposited in the grassed waterway due to consistently high hydraulic roughness throughout the year. Hence, a parsimonious approach solely relating annual erosion magnitude to SOC enrichment (e.g.…”
Section: Lateral C Fluxessupporting
confidence: 75%
“…However, this approach is likely to lead to biased estimates of both water-erosion-induced SOC redistribution and its effect on vertical C fluxes. Numerous studies have shown that the transport of SOC is selective (Schiettecatte et al, 2008), controlled by event characteristics (Sharpley, 1985;Van Hemelryck et al, 2010) and soil aggregation Kuhn, 2014, 2016). The enrichment of SOC during transport has been explicitly addressed by a few modelling studies, using different approaches Lacoste et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The relative extent of interrill compared with rill erosion depends upon local landscape and precipitation conditions, where higher precipitation intensity and steeper slopes can drive increased rill formation (Moody et al, 2013). The relative role of rill and interrill erosion can control the mobility of PyC throughout a landscape, as rill erosion likely would not preferentially transport PyC and would result in transport of bulk soil material (Schiettecatte et al, 2008), while sheet or interrill erosion can preferentially transport smaller, lighter, and organic-rich material (Wang et al, 2010).…”
Section: Post-fire Erosionmentioning
confidence: 99%